Dimethyl Ether Oxidation on an Active SnO2/Pt/C Catalyst for High‐Power Fuel Cells. Issue 9 (7th March 2019) - Kashyap, Diwakar; Teller, Hanan; Schechter, Alex
Abstract: Dimethyl ether (DME) has been considered a potential fuel for direct‐feed proton exchange membrane fuel cells, owing to its high energy density, low toxicity, and low crossover through a Nafion® membrane in comparison to commonly reported fuels such as methanol, ethanol, and formic acid. The main hurdle in the implementation of direct DME fuel cells is the sluggish oxidation kinetics on state‐of‐the‐art Pt−based catalysts (e. g. Pt and PtRu). In this work, DME oxidation on a platinum‐coated tin oxide catalyst (Pt/SnO2 ) supported on carbon is reported and compared with commercial Pt/C catalysts. Our catalyst was synthesized by using the polyol method, and structural characterization was performed by using transmission electron microscopy and X‐ray diffraction. Electrochemical analysis in acid solution showed overpotentials that are 50 mV lower than commercial Pt/C, as well as a higher oxidation current ( 44 m A P t - 1 ). The peak power obtained using a 4 cm 2 laboratory prototype fuel cell (loading of 1.23 mgPt  cm −2 on anode at 0.40 V) was 105 mW cm −2 at 70 °C. Online mass spectrometry analysis of the oxidation products gives insights into the new pathways of the electro‐oxidation mechanism on this promising catalyst. Abstract : Fuel for thought : Dimethyl ether (DME) is considered as a promising potential fuel in direct fuel cells. A platinum‐coated tin oxide catalyst support (Pt/SnO2 ) is found to be a highly efficient DME oxidation catalyst, which makes this fuel more viable for fuel cell systems.